Developing Smart Measurement Device to Measure Kinetic Friction Coefficients of Bi-Tilt Isolator - Ming-Hsiang Shih; Wen-Pei Sung (Advances in Civil Engineering)
A sliding vibration isolation system, affected by a kinetic friction force, provides a flexible or energy dissipation system for a structure. The kinetic friction coefficient of the contact surfaces between the moving parts changes with the relative moving velocity of the two contact surfaces. In this study, a smart measuring device is proposed to measure the kinetic friction coefficients of materials. The Arduino boards Arduino Nano, Arduino MPU-9250, and Arduino SD modules were combined to create this proposed smart device and mounted on three aluminum extrusions constructed as a horizontal platform. Then, varying amounts of steel gaskets were applied to adjust the various slopes for sliding tests. The time history of the acceleration and displacement responses of test object movements in the sliding process were respectively, recorded and detected by this proposed smart measuring device and the digital image correlation method (DIC). Statistical analyses of all test responses were used to derive the relationship of velocity to kinetic friction coefficient. Test and analysis results showed that (1) the relationship of velocity to kinetic friction coefficient for the conditions of mild lubrication and no lubrication displayed a trend of first decreasing and then increasing with increasing speed, respectively and (2) the relationship of velocity to kinetic friction coefficient for the condition of full lubrication revealed that the kinetic friction coefficient decreased with increasing speed. Test results demonstrated that this proposed smart measurement device, which is low in price and easy to assemble, can easily measure the kinetic friction coefficient of a material under various lubrication conditions.